GABI‐DUPLO: a collection of double mutants to overcome genetic redundancy in Arabidopsis thaliana. (7th May 2013) - Bolle, Cordelia; Huep, Gunnar; Kleinbölting, Nils; Haberer, Georg; Mayer, Klaus; Leister, Dario; Weisshaar, Bernd
Summary Owing to duplication events in its progenitor, more than 90% of the genes in the Arabidopsis thaliana genome are members of multigene families. A set of 2108 gene families, each consisting of precisely two unlinked paralogous genes, was identified in the nuclear genome of A. thaliana on the basis of sequence similarity. A systematic method for the creation of double knock‐out lines for such gene pairs, designated as DUPLO lines, was established and 200 lines are now publicly available. Their initial phenotypic characterisation led to the identification of seven lines with defects that emerge only in the adult stage. A further six lines display seedling lethality and 23 lines were lethal before germination. Another 14 lines are known to show phenotypes under non‐standard conditions or at the molecular level. Knock‐out of gene pairs with very similar coding sequences or expression profiles is more likely to produce a mutant phenotype than inactivation of gene pairs with dissimilar profiles or sequences. High coding sequence similarity and highly similar expression profiles are only weakly correlated, implying that promoter and coding regions of these gene pairs display different degrees of diversification.